Dalihan Na Tolu in the Dynamics of Toba Batak Identity Politics in the 2024 Regional Head Election in Pematangsiantar City - Ericson Muara Sianturi; Muhammad Rizwan; Dahlan A Rahman; Bimby Hidayat (Lembaga Kajian Sosial Politik Aceh (LaKaspia), 2026)
This study examines the role of Dalihan Na Tolu in shaping the dynamics of Toba Batak identity politics during the 2024 Regional Head Election (Pilkada) in Pematangsiantar City. It aims to analyze the models of identity politics and the factors influencing the transformation of Toba Batak identity politics throughout the electoral process. This study employed a qualitative method with a descriptive approach. Data were collected through in-depth interviews with 20 informants, including Toba Batak community members involved in the election, traditional leaders, religious leaders, punguan (clan associations), political party representatives, academics, and non-Toba Batak residents. The data were analyzed through data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation. The analysis was guided by theories of identity politics, political culture, political behavior, and the concept of regional head elections. The findings reveal that Toba Batak voters in Pematangsiantar City are no longer predominantly influenced by clan identity. Instead, their political preferences are increasingly shaped by religious identity politics and material-based political considerations. The emergence of rational-cultural voters and the growing influence of Christianity have further reduced the traditional role of clan affiliation in electoral decision-making. In addition, the findings indicate that public trust has fostered multicultural values amid the evolving political landscape. Overall, this study demonstrates a weakening of the traditional role of Dalihan Na Tolu in the dynamics of the 2024 Regional Head Election in Pematangsiantar City.